2010
DOI: 10.1103/physrevlett.104.137002
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Spin-Triplet Superconductivity in Co-Based Josephson Junctions

Abstract: We have measured a long-range supercurrent in Josephson junctions containing Co (a strong ferromagnetic material) when we insert thin layers of either PdNi or CuNi weakly-ferromagnetic alloys between the Co and the two superconducting Nb electrodes. The critical current in such junctions hardly decays for Co thicknesses in the range of 12-28 nm, whereas it decays very steeply in similar junctions without the alloy layers. The long-range supercurrent is controllable by the thickness of the alloy layer, reaching… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
547
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 556 publications
(564 citation statements)
references
References 31 publications
14
547
1
2
Order By: Relevance
“…78 The S/X/F/X/S junction may give an alternative route to realizing spin-triplet correlations inside a ferromagnet besides the use of noncollinear ferromagnets. 22,23 We also note that the spin-orbitassisted proximity-effect scenario considered here is different from the diffusive ferromagnet case, where the likely mechanism for proximity effect is believed to be the odd-frequency pairing. 23,24 The main argument for the odd-frequency superconductivity is that any anisotropic pairing would decay fast into a disordered metal on a length-scale of order a mean-freepath, while the odd-frequency isotropic pairing is immune from non-magnetic static disorder.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…78 The S/X/F/X/S junction may give an alternative route to realizing spin-triplet correlations inside a ferromagnet besides the use of noncollinear ferromagnets. 22,23 We also note that the spin-orbitassisted proximity-effect scenario considered here is different from the diffusive ferromagnet case, where the likely mechanism for proximity effect is believed to be the odd-frequency pairing. 23,24 The main argument for the odd-frequency superconductivity is that any anisotropic pairing would decay fast into a disordered metal on a length-scale of order a mean-freepath, while the odd-frequency isotropic pairing is immune from non-magnetic static disorder.…”
Section: Discussionmentioning
confidence: 75%
“…16 However, a number of recent experimental studies have demonstrated an unexpectedly long-ranged proximity effect in mesoscopic superconductor-ferromagnet hybrid structures. [17][18][19][20][21][22] There are a number of theoretical scenarios which can explain this phenomenon. In most of the scenarios pair correlations inside the ferromagnet are attributed to some type of equal-spin triplet pairing.…”
Section: Introductionmentioning
confidence: 99%
“…At a superconductor/ferromagnet (S/F) junction conventional spin-singlet Cooper pairs penetrating into the ferromagnet will decay over a length of the order of due to destruction of the Cooper pair coherence as a result of the exchange field of the ferromagnet 1 (where is the diffusion coefficient and is the exchange energy in the ferromagnet 2,3 ). In strong ferromagnets is large and is of the order of ~1 nm at low temperature ; however, theories have emerged recently suggesting the existence of a novel proximity effect where spin-triplet pairing is generated at the S/F interface resulting in a greatly extended decay length, .…”
Section: Introductionmentioning
confidence: 99%
“…22 Once generated, triplet correlations can penetrate over long distances into ferromagnets as observed in experiments on SFS Josephson junctions. [23][24][25][26] These experiments suggest the possibility of using SF hybrids in spintronic circuits with the aim of lowering the dissipation. 4 On the other hand, the study of heat transport in nanoscale devices, i.e., caloritronics, also attracts the attention of researchers working on nanodevies [27][28][29] containing, for example, normal metal, ferromagnets 30,31 and superconductors.…”
Section: Introductionmentioning
confidence: 99%
“…In order to detect the spin triplet supercurrents, the longrange Josephson effect has been measured in a variety of multilayered ferromagnetic structures 24,25,55,56 with inhomogeneous magnetic configurations. According to the theoretical prediction, 3 such inhomogeneity induces the triplet pair correlations with equal spin projection in the ferromagnetic bridge.…”
Section: B Triplet Josephson Junctions With Spin Filtermentioning
confidence: 99%